2020
DOI: 10.1073/pnas.2001348117
|View full text |Cite
|
Sign up to set email alerts
|

Fast spiking interneuron activity in primate striatum tracks learning of attention cues

Abstract: Cognitive flexibility depends on a fast neural learning mechanism for enhancing momentary relevant over irrelevant information. A possible neural mechanism realizing this enhancement uses fast spiking interneurons (FSIs) in the striatum to train striatal projection neurons to gate relevant and suppress distracting cortical inputs. We found support for such a mechanism in nonhuman primates during the flexible adjustment of visual attention in a reversal learning task. FSI activity was modulated by visual attent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…We next asked whether the narrow spiking, putative interneurons that encode p (choice) in LPFC and RPE in ACC are from the same electrophysiological cell type, or e-type (Markram et al, 2015). Prior studies have distinguished different narrow spiking e-types using the cells’ spike train pattern and spike waveform duration (Ardid et al, 2015; Dasilva et al, 2019; Trainito et al, 2019; Banaie Boroujeni et al, 2020b). We followed this approach using a cluster analysis to distinguish e-types based on spike waveform duration parameters (inferred hyperpolarization rate and time to 25% repolarization), on whether their spike trains showed regular or variable interspike intervals (local variability ‘ LV ’), or more or less variable firing relative to their mean interspike interval (coefficient of variation ‘ CV ’).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next asked whether the narrow spiking, putative interneurons that encode p (choice) in LPFC and RPE in ACC are from the same electrophysiological cell type, or e-type (Markram et al, 2015). Prior studies have distinguished different narrow spiking e-types using the cells’ spike train pattern and spike waveform duration (Ardid et al, 2015; Dasilva et al, 2019; Trainito et al, 2019; Banaie Boroujeni et al, 2020b). We followed this approach using a cluster analysis to distinguish e-types based on spike waveform duration parameters (inferred hyperpolarization rate and time to 25% repolarization), on whether their spike trains showed regular or variable interspike intervals (local variability ‘ LV ’), or more or less variable firing relative to their mean interspike interval (coefficient of variation ‘ CV ’).…”
Section: Resultsmentioning
confidence: 99%
“…Prior experimental studies have suggested that interneurons have unique relationships to oscillatory activity (Puig et al, 2008;Cardin et al, 2009;Sohal et al, 2009;Vinck et al, 2013;Womelsdorf et al, 2014a;Chen et al, 2017;Voloh and Womelsdorf, 2018;Shin and Moore, 2019;Banaie Boroujeni et al, 2020b;Onorato et al, 2020), raising the possibility that the N3 e-type neurons realize their functional contributions to p(choice) and RPE processing also through neuronal synchronization. To discern this, we first inspected the spike-triggered LFP averages (STAs) of neurons and found that STAs of many N3 e-type neurons showed oscillatory sidelobes in the 10-30 Hz range (Fig.…”
Section: Classification Of Neural Subtypes Of Putative Interneuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the striatum lesions abolish selectively the ability to use reward incentives to optimize decisions (Schmidt et al, 2008). Intermingled with reward incentive coding neurons in the striatum are neurons of the so-called no-go pathway that learn to activate in response to aversive, undesired stimuli -including distractor events -in order to inhibit action or attention to them (Burke et al, 2017;Arcizet and Krauzlis, 2018;Banaie Boroujeni et al, 2020). This inhibitory striatal pathway receives input from medial prefrontal cortex where localized clusters of neurons mediate avoidance behavior to stimuli with negative outcome associations (Amemori and Graybiel, 2012;Amemori et al, 2020) and represent negative prediction errors that are specific to incorrectly attended visual object features (Oemisch et al, 2019).…”
Section: Expecting Gains Enhances Attentional Efficacy But Can't Compmentioning
confidence: 99%
“…Alternatively, the dependence on the action selection mode may reflect an attentional component of the task. Recently, a study in the monkey reported that striatal FSIs modulate their activity during an oculomotor task according to the amount of attention allocated to stimuli (Banaie Boroujeni et al., 2020). In our experiment, it is conceivable that attention is higher in the external condition in which monkeys were required to allocate attention to detect and report the location of the trigger stimulus presented pseudorandomly in one of two locations and this difference may bring about an increased level of FSI activity.…”
Section: Discussionmentioning
confidence: 99%